Peran Guru Akidah Akhlak Dalam Membentuk Karakter Siswa Kelas III MI - Mar'atussholehah Mar'atussholehah (IBTIDAIYAH: Jurnal Penelitian dan Pendidikan Dasar Islam, 2025)
This study investigates the role of Akidah Akhlak teachers in shaping the character of third-grade students at MI Nurussa’adah Air Hitam Sarolangun, as well as the supporting and inhibiting factors in its implementation. The purpose of this research is to understand how Akidah Akhlak teachers carry out their role in character development, and to evaluate the alignment with Thomas Lickona’s character education theory. This research employs a field study approach using qualitative descriptive methods. Data were collected through observation, interviews, and documentation. The results show that Akidah Akhlak teachers at MI Nurussa’adah have fulfilled their role in character development through role modeling, habituation, and enforcement of discipline, in line with the concepts of moral knowing, moral feeling, and moral action from Thomas Lickona’s theory.